John Watson Foster papers - Foster, John Watson, 1836-1917.
Chiefly letters received (1872-1905) relating to Indiana politics, Republican Party, Alaska-Canadian boundary dispute, sealing rights in the Bering Sea, and diplomatic relations with Mexico, Russia, Spain, and China. Correspondents include James Gillespie Blaine, Schuyler Colfax, William Maxwell Evarts, Walter Quintin Gresham, Benjamin Harrison, John Hay, Richard Olney, Whitelaw Reid, and Theodore Roosevelt.
Diplomat, U.S. secretary of state, lawyer, and publisher.
Collection material in English.
Keywords: Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Evarts, William Maxwell, -- 1818-1901 -- Correspondence; Gresham, Walter Quintin, -- 1832-1895 -- Correspondence; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Olney, Richard, -- 1835-1917 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; United States. -- Department of State; Republican Party (U.S. : 1854- ); Bering Sea controversy; Diplomatic and consular service, American; Sealing -- Bering Sea; Alaska -- Boundaries -- Canada; Canada -- Boundaries -- Alaska; China -- Foreign relations -- United States; Indiana -- Politics and government; Mexico -- Foreign relations -- United States; Russia -- Foreign relations -- United States; Spain -- Foreign relations -- United States; United States -- Foreign relations -- Mexico; United States -- Foreign relations -- Russia; United States -- Foreign relations -- Spain; United States -- Foreign relations -- China; Cabinet officers; Diplomats; Lawyers; Publishers